Evaluation of clinical efficacy and safety of Bibrocathol 2% eye ointment in the treatment of Chronic Blepharoconjunctivitis - Elena Yani; Sergey Astakhov; Vladimir Brzheskiy; Evgeniy Egorov; Alexey Seleznev; Dorothea Groß; Heidi Opitz (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2022)
Purpose: To assess the efficacy and safety of bibrocathol 2% eye ointment in patients with chronic blepharoconjunctivitis.  Materials and methods: This was a multi-center, randomized, double-masked, placebo-controlled, parallel-group, phase III study. Patients with chronic blepharoconjunctivitis were randomized to apply either bibrocathol 2% (n = 100) or placebo (n = 100) three times a day for 14 days. The primary efficacy endpoint was the change from baseline to Day 15(+1 day) in the total score of signs summarizing the investigators' assessment of the severity of lid oedema, lid erythema, debris, hyperemia, and pouting of Meibomian glands based on slit-lamp examination (modified Intention-to-treat (mITT) set). Safety endpoints included visual acuity, intraocular pressure, and adverse events. Investigators and patients performed an overall assessment of treatment tolerability. Results: On Day 15(+1 day) the least square (LS) mean change from baseline in the total sum score of signs was -8.62 (95% CI: -9.16; -8.08) in the bibrocathol group and -6.00 (95%CI: -6.54; -5.45) in the placebo group. The LS means the difference between treatment groups was statistically significant in favor of bibrocathol (-2.63 [95% CI: -3.36, -1.89], p < 0.001). Bibrocathol was statistically significantly superior to placebo in reduction of the individual ocular signs scores and the patient's-assessed ocular discomfort severity (p < 0.001). No safety issues were observed concerning visual acuity, intraocular pressure, and the occurrence of adverse events. Conclusions: The study showed superior efficacy of two weeks of treatment with bibrocathol versus placebo in reducing signs and symptoms of chronic blepharoconjunctivitis. Treatment with bibrocathol 2% eye ointment was safe and well-tolerated.